Synthesis, spectroscopic studies and electrochemical properties of Schiff bases derived from 2-hydroxyaldehydes and phenazopyridine hydrochloride - Yagmur Sultan; Yilmaz Selehattin; Saglikoglu Gulsen; Sadikoglu Murat; Yildiz Mustafa; Polat Kamran (Journal of the Serbian Chemical Society, 2013)
Novel Schiff bases (1-4) were synthesized by the reaction of 2-hydroxybenzaldehyde, 2-hydroxy-5-methoxybenzaldehyde, 2-hydroxy-5-nitrobenzaldehyde, 2-hydroxy-1-naptaldehyde with phenazopypridine hydrochloride (PAP) and their structures were elucidated by means of spectroscopic techniques. The electrochemical reduction of PAP and its Schiff bases (1-4) were carried out on glassy carbon electrode (GCE) in dimethyl sulfoxide (DMSO) using the cyclic voltammetric (CV) technique. The effect of functional groups on reduction potential of Schiff bases was investigated. A general electrochemical reduction mechanism of the compounds was also suggested.